Analysis on epidemiological and drug resistance characteristics of lymph node tuberculosis from Hunan province, China - Tanwei Fang; Yu Xiang; Yu Xiang; Wenbin Li; Binbin Liu; Haican Liu; Yaning Wu; Da Xu; Machao Li; Shuliu Yang; Shuliu Yang; Jixiang Li; et al. (Frontiers Media S.A., 2024)
ObjectivesTo investigate the clinical epidemiological and drug resistance (DR) characteristics of lymph node tuberculosis (LNTB) in Hunan Province which locates in South-central China, and to provide scientific clues for effective prevention and treatment of LNTB.MethodsWe retrospectively collected LNTB patients with Mycobacterium tuberculosis culture positive at Hunan Chest Hospital, the biggest TB reference hospital in South-central China, from January 2013 to December 2021. The multiple demographic, clinical and drug susceptibility data of patients were collected from the hospital's electronic patient records. Descriptive statistical methods, Chi-square test and logistic regression analysis were employed as statistical methods.ResultsOf the 577 LNTB cases, 373 (64.64%) were males, 352 (61.01%) were farmers; majority (161, 33.10%) aged at 20-29 years old; 147 (25.48%) had simple LNTB, 350 (60.66%) had LNTB combined with pulmonary TB (PTB) (defined as LNTB-PTB), and 80 (13.86%) had LNTB combined with other extrapulmonary TB (EPTB) (defined as LNTB-EPTB). A total of 345 (59.79%, 345/577) LNTB patients had cervical node infection, and the simple LNTB patients (81.63%, 120/147) had higher proportion of this infection than LNTB-PTB (51.71%, 181/350) and LNTB-EPTB (55.00%, 44/80) (both p values <0.017), respectively. LNTB-EPTB was more inclined to have abdominal tuberculous LNs (20%, 16/80) and at least four tuberculous lesions (22.50%, 18/80) than simple LNTB and LNTB-PTB. Seventy-seven (13.34%) and 119 (20.62%) were resistant to rifampicin (RIF) and isoniazid (INH), respectively; 72 (12.48%) were multi-drug resistant (MDR), and a total of 150 (26.00%) were DR (resistant to at least one of RIF, INH, ethambutol and streptomycin). LNTB patients aged 30-34 and 50-54 years old (compared to those aged <30 years) were independent predictors of RIF resistance (RR) (ORs were 3.47 and 2.83, respectively; 95% CIs were 1.64-7.35 and 1.08-7.46, respectively).ConclusionOur study disclosed the epidemiological and DR characteristics of LNTB in Hunan Province, China. High LNTB prevalence was found in younger people while high RR LNTB prevalence was found in older ones, suggesting that we should conduct further studies to clarify the occurrence of RR in LNTB, meanwhile, strengthen the diagnoses and treatments of LNTB to prevent the emergence of RR.